Determining the effect of a non-uniform AGB outflow on its chemistry. Issue Volume 13:Issue S332(2017) (4th September 2018) - Van de Sande, M.; Sundqvist, J. O.; Millar, T. J.; Decin, L.
Abstract: The molecular composition of the stellar outflows of AGB stars is determined by the stellar elemental carbon-to-oxygen abundance ratio, together with the physical circumstances in the innermost region of the outflow. Near the stellar surface, thermal equilibrium (TE) can be assumed. This leads to a certain molecular composition with a O- or C-rich signature. However, several molecular species have been detected that are not expected to be present in the inner region under the assumption of TE chemistry. As a solution to explain the presence of these unexpected species, non-equilibrium chemistry in the inner region of the outflow has been proposed. The outflows of AGB stars are generally not spherically symmetric or homogeneous, which influences the penetration of interstellar UV photons throughout the outflow. We investigate the effect of a clumpy, non-homogeneous outflow on the composition of the inner region by introducing a simple porosity formalism in our chemical model.